INNOVATIVE APPROACHES TO PROVIDING SOCIO-POLITICAL ACTIVITY OF YOUTH ORGANIZATIONS IN UZBEKISTAN (Conferencea, 2023)
The tomorrow of our country, an important force that brings about changes in the society, bringing creative ideas to life, morally and socially supporting young people, who are considered a resource with spiritual potential, by creating favorable conditions for them to occupy a worthy place in society, turning them into a great force that decides the fate and future of the country are important tasks of each of us. The article discusses the dynamics of institutionalization of social and political activity of young people in Uzbekistan.